Digital Products Increase Fee-based Income Banking in Indonesia - Ossi Ferli; Desi Lestari; Luh Ifaterani Isabrenda Kusumawardhani (Jurnal Ilmu Manajemen & Ekonomika, 2022)
This study aims to analyze the effect of digital innovation on fee-based income for five commercial banks listed on the Indonesia Stock Exchange for the 2015-2019 period. The analytical tool used in this study is panel multiple regression equations with the dependent variable feebased income and the dependent varia-ble Number of ATMs, CRM & CDM, Number of SMS, transactions Internet and Mobile Banking, Number of Branches. The results showed that Branches has an insignificant effect on fee-based income. The num-ber of ATMs, CRM & CDM, and the number of SMS, Internet and Mobile Banking transactions has a sig-nificant positive effect on fee-based income. This indicates that digital innovation in banking can increase the bank's fee-based income.